MENATA FIQH DAKWAH DALAM PENYULUHAN - Fauzi Saleh (Universitas Islam Negeri Ar-Raniry, 2012)
Social problems appeared because of unawareness of the case root. If it can be traced back, it makes easier to cure as social therapy. Islamic concept of this called da’wah that not only by mean of preaching but the attitude and action. Fiqh da’wah (model of preaching) in Islam must be based on the principle and method. Among the principle are bil hikmah (wisdom), maw’idhah (lesson) and mujadalah bil hasan (the good way of debate). Meanwhile da’wah should be based on the management such planning, acting and evaluating. Da’wah without these principles and methods will be effective especially in this era.